Perlindungan Data Pribadi dalam Kegiatan Peer to Peer Lending - Rachayu, Vika; Hidayat, Muhammad Fajar (Penerbit Goodwood, 2023)
Purpose: The research objective to be achieved in this study is to determine the protection of personal data in peer to peer lending activities. In this data analysis technique, researchers use research materials in the form of books, journals, documents and research results obtained from a literature review. Methodology: In the data analysis technique, the data obtained will be analyzed using qualitative methods. The qualitative method is observing in their environment by interacting and trying to understand language and interpretations of the world around them. Results: Information technology-based service providers through online, have an obligation to meet personal data protection standards. Protection of personal data is one of the most important things in conducting online transactions, because personal data is related to user security. Limitation: This research contributes to the government and the community must be able to act more thoroughly, meticulously and have a prudent nature, especially when carrying out technology-based lending and borrowing services. Contribution: It is hoped that this law will become a strong legal umbrella for the management and protection of citizens' personal data and government administrators.